Anesthetic Challenges in Hirayama Disease Patients Undergoing Cervical Spine Surgery—A Case Series - Sreyashi Naskar; Soumya Chakrabarti; Dipanjan Dawn; Amita A. Pahari (Journal of Neuroanaesthesiology and Critical Care)
Hirayama disease (HD) is a rare disease, resulting from cervical compressive myelopathy, manifesting as upper limb muscular atrophy, and rarely autonomic and upper motor neuron signs. Anesthesia management is challenging—careful neck positioning during bag-mask ventilation and endotracheal intubation, avoidance of drugs that release histamine, multimodal monitoring to avoid delayed recovery, anticipation of hypotension, and blood loss due to autonomic dysfunction—all this is necessary for successful outcome of general anesthesia in HD patients. This case series demonstrates that preexisting autonomic dysfunction in HD patients should alert the anesthesiologists regarding higher likelihood of hemodynamic perturbations and blood loss, compared with patients who have normal autonomic functions, and henceforth take appropriate precautionary measures.